Effect of Different Amounts Of Zeolite On The Growth Of Catfish With A Recirculation System - Muhammad Suandi; Mulyadi Mulyadi; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted from September to October 2018 in the Technical Service Unit of Hatchery at the Faculty of Fisheries and Marine, University of Riau. The purpose of this study is to determine the amount of zeolite in the filter to increase the growth of Pangasius hypothalamus which are maintained by a recirculation system. This method uses an experimental method with 4 levels of treatment and 3 replications. The treatment is P0 Control (without zeolite); P1 600 g; P2 700 g and P3 800 g. The test fish used was Siamese catfish with a size of about 5-6 cm and maintained for 40 days. The results showed that the best treatment was the amount of zeolite 800 g,water quality such as temperature 27-280 C, pH 5.66-6.86, dissolved oxygen 5.78-5.63 mg / l, ammonia (NH3) 0.004-0.022 mg/L, nitrite (NO2) 0.0030-0.034 mg/L, nitrate (NO3) 0.54-1.56, absolutegrowth weight is 5.26 g, absolute growth length 4.67 cm, specific growth rate of 3.23%,survival rate of 100 % and feed efficiency of 94.09%. Key words : Zeolite, Recirculation, Growth, Pangasius hypopthalmus